Analisis Kelayakan Usaha Pada UMKM Kopi Estona Kabupaten Jember - Ridho Septian Waluyo; Putri Sefy Dwi Hadiyana; Fadilla Sindi Aprilia Putri; Sally Tri Utami; Daniah Trina Jessica; Jasmine Diva Fia Rosida (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This research focuses on business feasibility analysis for Estona Coffee MSMEs in Jember Regency, East Java. This research contains a profile of MSMEs and several aspects therein such as licensing aspects, production technical aspects, marketing aspects, management aspects and financial aspects. Not only that, this research also examines the economic, social and environmental aspects of Estona Coffee MSMEs in Jember Regency, East Java. This research uses qualitative methods through interviews where the interviews focus on the owners of Estona Coffee MSMEs located in Jember Regency, East Java. This research produces analytical responses regarding the business feasibility of Estona Coffee MSMEs in Jember Regency, East Java.